Analisis Promosi Venue Pameran di Kota Depok Studi Kasus Venue The Margo Hotel - Syafira Indah Pertiwi; Firman Syah (Bisnis Event, 2023)
Depok has many options of venues for holding an event. Nowadays, Depok has managed to be more active in promoting the available venue and accommodation. This research aims to explain the readiness of The Margo Hotel and the role of city government in collaboration with holding an event in Depok. During the research process, the author found that organizing a large-scale exhibition in Depok must have a suitable venue in terms of facilities, capacity, and accommodation. The Margo Hotel is one of the potential venues for holding exhibitions in Depok. This research used a qualitative approach with a type of descriptive research. The data collection was obtained from an interview process with The Margo Hotel and the Youth, Sports, Culture, and Tourism Office of Depok also observing the venue. On the other hand, the secondary data had obtained from The Margo Hotel documents. This research showed that the Youth, Sports, Culture, and Tourism Office of Depok has established a website as one of the promotional efforts for MICE and Tourism activities in Depok. These promotional efforts aim to develop the collaboration between stakeholders and the city government to make exhibitions in Depok, specifically for holding large-scale exhibitions.